A Rare Case of Cecal Bascule in a Child With Normal Neurodevelopment. Issue 3 (March 2020) - Loureiro, Sandra Oliveira; Lynch, Timothy; Medeiros, Braeden John; Merritt, Neil; Lim, Rodrick
Abstract : Abstract: Cecal volvulus is a rare cause of bowel obstruction in adults and an extremely rare presentation in children. One form known as a cecal bascule has only previously been reported in children with neurodevelopmental issues or with severe chronic constipation. We present the case of a 10-year-old boy who presented with an acute history of left lower quadrant abdominal pain, who upon investigation was found to have a cecal bascule.